2013
DOI: 10.2214/ajr.12.9260
|View full text |Cite
|
Sign up to set email alerts
|

Appendiceal Mucocele: A Diagnostic Dilemma in Differentiating Malignant From Benign Lesions With CT

Abstract: Differentiating malignant from benign mucoceles can be difficult with CT. Irregular walls and soft-tissue thickening are features most likely to be associated with malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
55
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 18 publications
4
55
0
9
Order By: Relevance
“…Soft-tissue thickening inside the appendix, wall irregularity, or presence of PMP have been shown to be the most reliable markers for malignancy. [8]…”
Section: Discussionmentioning
confidence: 99%
“…Soft-tissue thickening inside the appendix, wall irregularity, or presence of PMP have been shown to be the most reliable markers for malignancy. [8]…”
Section: Discussionmentioning
confidence: 99%
“…CT appearances preoperatively usually show a round, cystic tubular mass in the location of the appendix [15]. Mucoceles are well-encapsulated with a smooth wall of variable thickness [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, differentiating between benign and neoplastic mucoceles preoperatively is more difficult. A limited study by Wang et al in 2013 suggested that irregularity and soft tissue thickening can suggest a preoperative diagnosis of appendiceal mucocele but the study excluded patients presenting with appendicitis, ruling out a large proportion of cases [15]. …”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that CT is better than ultrasound (US) and magnetic resonance imaging (MRI) to diagnose mucocele: however, it is difficult to distinguish between benign and malignant neoplastic mucoceles [9,[15][16][17]. Mucinous Appendiceal mucocele requires surgical resection.…”
Section: Discussionmentioning
confidence: 99%